Real-time PCR method for the detection of the gene encoding surface lipoprotein LipL32 of pathogenic Leptospira: use in the laboratory diagnosis of the acute form of leptospirosis - Cermakova, Zuzana; Kucerova, Petra; Pliskova, Lenka; Kubickova, Pavla (Scandinavian journal of infectious diseases, 2013)
BACKGROUND: The aims of this work were to replace the obsolete PCR method for the laboratory diagnosis of the acute form of leptospirosis using the G1, G2 and B64 I, B64 II primers, and to improve the PCR detection time. METHODS: We introduced a real-time PCR method for the detection of the gene encoding the surface lipoprotein LipL32 of pathogenic Leptospira into our laboratory diagnosis of the acute form of leptospirosis. The positive and negative analytical specificities of the real-time PCR method were both equal to 100%; the detection limit was determined to be 1-5 genome copies/1 ml of liquid biological material. The method was further validated on 230 laboratory strains of leptospires. RESULTS: All laboratory strains of pathogenic Leptospira were evaluated as LipL32-positive and all non-pathogenic strains as LipL32-negative. In addition, 455 biological materials (253 plasma, 121 urine, 72 cerebrospinal fluid (CSF), 7 bronchoalveolar lavage, and 2 sputum) from 295 patients with suspected leptospirosis were examined. From this set of patients, 9 were evaluated to be LipL32-positive, from 15 positive biological materials (10 urine, 4 blood plasma, and 1 CSF). CONCLUSIONS: This real-time PCR method for the detection of the gene encoding the surface lipoprotein LipL32 is a reliable, sensitive, and rapid method for the detection of the acute form of leptospirosis.
Keywords: Sensitivity and Specificity; senzitivita a specificita; Molecular Diagnostic Techniques; Humans; Leptospirosis; lidé středního věku; diagnostické techniky molekulární; Lipoproteins; Leptospira; Female; Aged; mladý dospělý; dospělí; klinické laboratorní techniky; Bacteriological Techniques; senioři; lidé; časové faktory; Bacterial Outer Membrane Proteins; Adult; proteiny vnější bakteriální membrány; ženské pohlaví; Male; Middle Aged; Clinical Laboratory Techniques; Real-Time Polymerase Chain Reaction; Young Adult; leptospiróza; lipoproteiny; mužské pohlaví; Time Factors; kvantitativní polymerázová řetězová reakce; bakteriologické techniky